2020
DOI: 10.1111/joim.13019
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of myeloproliferative neoplasms – trends by subgroup and age in a population‐based study in Sweden

Abstract: Background The reported incidence of Philadelphia‐negative myeloproliferative neoplasms (MPNs) differs substantially between previous reports, likely due to true regional differences in incidence and/or variations in the quality and coverage of the cancer registers. Objective We therefore assessed MPN incidence in Sweden during recent years using prospectively collected information captured in Swedish health registers. Methods Patients with MPNs were identified through the Swedish Cancer Register and Swedish B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
17
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 28 publications
5
17
1
5
Order By: Relevance
“…Our study shows male-to-female ratio to be 1.2, which is compatible with a Norwegian study male-to-female ratio is 1.2 for all MPNs [8]. Another Swedish study has shown male-to-female ration as 1.07 [9].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our study shows male-to-female ratio to be 1.2, which is compatible with a Norwegian study male-to-female ratio is 1.2 for all MPNs [8]. Another Swedish study has shown male-to-female ration as 1.07 [9].…”
Section: Discussionsupporting
confidence: 91%
“…Regarding PV, our study shows male-to-female ratio to be 2. This is compatible with the US study that shows a ratio of 1.83 [11], while the Swedish study reported a ratio of 1.48 [9].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similarly, incidence of PMF increased slightly over time [ 14 ]. The number of MPN patients who were recorded as unclassified decreased over time demonstrating an improvement in the classification of cases [ 15 ]. Conversely, in Australia, between 2003 and 2014, incidence of MPNs have been seen to decrease by −2.9% per year [ 16 ].…”
Section: Incidence and Prevalence Of Mpnsmentioning
confidence: 99%
“…Myeloproliferative neoplasms (MPN) are a collection of clonal hematopoietic stem cell disorders characterized by the proliferation of one of more of the hematopoietic lineages [ 1 , 2 , 3 , 4 ]. The major clinicopathologic entities comprise chronic myeloid leukemia (CML), polycythemia vera (PV), essential thrombocythemia (ET), and primary myelofibrosis (PMF) [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%